LITERACY SKILLS DEVELOPMENT THROUGHT MESSANGERS' STORIES AS THE SPIRITUAL BEHAVIOUR REALISATION IN ELEMENTARY SCHOOL - Mayarnimar Mayarnimar; Taufina Taufina; Muhammadi Muhammadi; Muhammad Ilham Syarif (Universitas Pahlawan Tuanku Tambusai, 2019)
The aim of this study is development literacy with using the story of the prophet to made good spiritual attitude valid for elementary school, practice, and efective. Methods This study use the development of research of Plomp. This study is a research design that combines Plomp models with models Gravemeijer & Cobb, the which consists of 3 phases roomates preliminary studies (Preliminary research / preparing for the experiment), phase of development (Development or prototyping phase / design experiment) and assessment phase ( assessment phase / retrospective analysis), This population is elementary school in Padang. The results Showed that the learning literacy with using the story of the prophet to made good spiritual attitude for elementary student get 95.5% is Valid. literacy with using the story of the prophet to made good spiritual attitude get practice for elementary student questionnaire teacher get 87.5%, 83.3% of the student questionnaire. literacy with using the story of the prophet to made good spiritual attitude for elementary student can get effective Because student chose how to implemented a spiritual good in their attitude after literacy live with the story of prophet.